Commissioning of the Radiation Monitor Calibration Laboratory (LabCal) of IDQBRN for cesium-137 irradiation system (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The provision for the Brazilian Army of equipment that provides reliable and safe measurements, enabling decision-making based on radioprotection parameters, leads to the need to investigate the metrology of the calibration system used in the Radiation Monitor Calibration Laboratory (LabCal) of the Institute of Chemical, Biological, Radiological and Nuclear Defense (IDQBRN). To this end, the commissioning in cesium-137 is of primary importance in this process. In order to check the conformity of the radiator system, in this work, the ambient dose equivalent rate, , was obtained experimentally for several configurations to compare them with the appropriate theoretical concepts. For this, the distance between the source of Cesium-137 (36.9 GBq in 01/22/2015) and the ionization chamber was varied from 500 to 3000 mm at 250mm intervals. To obtain lower ambient dose equivalent rates, 15 and 32 mm thick lead attenuators were used. The mathematical model that best fit the experimental values was analyzed. In all cases, the potential function offers better fit, since the coefficients of determination obtained are approximately equal to 1, obeying the Law of the Inverse Square of the Distance, according to theoretical foundation. Moreover, it was evaluated that the relative deviations are below the limits established by the relevant standard.